Pengaruh Key Performance Indicator Dan Sistem Pengendalian Manajemen Terhadap Kinerja Karyawan - Fajar Danang Dwi Asmoro; Shinta Ningtiyas Nazar (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to analyze the influence of Key Performance Indicators (KPI) and Management Control Systems on employee performance at Bank MNC. Using a quantitative approach, the research involved 40 respondents from the bank's employees. The sampling method employed was saturation sampling. The methods used in this study include descriptive analysis, data instrument tests, classical assumption tests, multiple regression analysis, and hypothesis testing, with data processing conducted using SPSS version 26.the results of the partial hypothesis test indicate that Key Performance Indicators significantly influence employee performance, while Management Control Systems also partially influence employee performance. Meanwhile, the results of the simultaneous hypothesis test show that Key Performance Indicators and Management Control Systems simultaneously influence the performance of Bank MNC employees. This study provides valuable insights for Bank MNC's management in developing more effective managerial strategies to create a work environment that supports employee development